49. THE MOUTHWASH CONTAINING CHLORHEXIDINE AND CHLORINE DIOXIDE: AN IN VITRO STUDY (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effect of the mouthwash containing chlorhexidine and chlorine dioxide on human gingival fibroblasts.Subject and method: The impact of mouthwash containing both chlorhexidine (concentrations from 0.01, 0.02, 0.05, 0.1, and 0.2%) and chlorine dioxide (0.05 and 0.1%) on human gingival fibroblasts after 24 hours of contact was assessed using the colorimetric assay MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide], in accordance with ISO10993-5:2009.Results: After 24 hours of contact, the mouthwash containing chlorhexidine and chlorine dioxide showed toxicity grades 3 and 4 to the human gingival fibroblast.Conclusion: The mouthwash containing chlorhexidine and chlorine dioxide was toxic to human gingival fibroblasts after 24 hours of exposure.
Keywords: chlorhexidine; chlorine dioxide; human gingival fibroblast; mouthwash.